ANALISIS PENGAWASAN TATA KELOLA KOPERASI DALAM MENINGKATKAN AKUNTABILITAS PADA KSP KOPDIT PINTU AIR CABANG KEWAPANTE - Magdalena Femilia Nean; Andreas Rengga; Wihelmina Maryetha Yulia Jaeng (Jurnal Projemen UNIPA, 2025)
This research aims to analyze the goverance oversight mechanisms employed to enhance accountabillity at Pintu Air Credit Union, Kewapante Branch. A qualitative descriptive analysis approach was utilized, incorporating observation, interviews, and documentation as primary data collection techniques. The data sources comprised both primary and secondary data. The study involved five key informants: the Manager of Pintu Air Credit Union, Kewapante Branch, the supervisor, the Committee Chairperson, the Committee Vice-Chairperson, and the Account Officer. The findings reveal that Pintu Air Credit Union, Kewapante Branch, has established a disciplined internal oversight andof reporting system that promotes transparency while minimizing confilicts interest. Accountability is evidenced through comprhensive transactionaudits and robust internal control mechanisms. Responsibility in Pintu Air Credit Union, Kewapante Branch is seen in the obligations of each employee, especially in the inspection process affter collection to ensure that all transctions are recored correctly. The independence of both internal and external audits faclitates effective risk management. Fairness is evident in the organization’s open recruitment processes and equitable competency developments programs.